The role of prostanoids in regulatory T cells and their implications in inflammatory diseases and cancers - Somsak Prasongtanakij; Kitipong Soontrapa; Dean Thumkeo (European Journal of Cell Biology)
Regulatory T cells (Tregs) play an important role in the immune system through the regulation of immunological self-tolerance and homeostasis. Furthermore, increasing evidence suggests the potential contribution of Tregs beyond immunity in the process of repairing various injured tissues. Tregs are generally characterised by the constitutive expression of forkhead box protein 3 (FOXP3) transcription factor in the nucleus and high expression levels of CD25 and CTLA-4 on the cell surface. To date, a large number of molecules have been identified as key regulators of Treg differentiation and function. Among these molecules are prostanoids, which are multifaceted lipid mediators. Prostanoids are produced from arachidonic acid through the catalytic activity of the enzyme cyclooxygenase and exert their functions through the 9 cognate receptors, DP1‐2, EP1-EP4, FP, IP and TP. We briefly review previous studies on the regulatory mechanism of Tregs and then discuss recent works on the modulatory role of prostanoids.